Driving fiber with pH response and preparation method thereof

By introducing tanninic acid modified polymer A/polyvinyl alcohol complex into the fibers, the pH value is used to regulate the shrinkage and elongation of the fibers, the problem of driving mechanism in the prior art is solved, and the problem of unidirectional at different pH values ​​is achieved diversity and selective driving effects under the .

CN119491413AActive Publication Date: 2025-02-21DONGHUA UNIV

Patent Information

Application Number
CN202411622801.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-21
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The lack of a pH drive system in the prior art that can shrink in alkaline solutions and elongate in acidic solutions leads to one-way driving mechanisms and it is difficult to accurately control local and global movements.

Method used

The polymer A/polyvinyl alcohol composite fibers modified with tannin acid are used to regulate the shrinkage and elongation of the fibers at different pH values ​​through the protonation and deprotonation reaction of the side chain amine group of the polymer A side chain.

Benefits of technology

The properties of shrinking in an alkaline solution with pH value ≤11 and elongating in an acidic solution with pH value ≥1 were achieved. The fibers maintained stable work density and mechanical properties during 10 acid-base cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491413A_ABST
    Figure CN119491413A_ABST
Patent Text Reader

Abstract

The invention relates to a pH-responsive driving fiber and a preparation method thereof. The pH-responsive driving fiber has the properties of shrinking in an alkaline solution with the pH value being less than or equal to 11 and stretching in an acidic solution with the pH value being greater than or equal to 1. The driving fiber with pH response is a tannic acid modified compound fiber, and the compound fiber is a polymer A / polyvinyl alcohol compound fiber; the polymer A is a polymer with amido on a side chain; the preparation method comprises the following steps: immersing the polymer A / polyvinyl alcohol compound fiber into a tannic acid solution for swelling, regulating the pH value of the solution to 8-9, heating to 50-60 DEG C, introducing oxygen, carrying out covalent cross-linking reaction between the tannic acid and the polymer A in an oxygen atmosphere, washing the reacted product with deionized water, and drying to obtain the product. The preparation method is simple; the prepared product can effectively control the extension and contraction behaviors by controlling the pH value of a solution, and has a relatively high driving rate in strong acid and strong alkali.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of artificial driving materials and relates to a driving fiber with pH response and a preparation method thereof. Background Art

[0002] Actuators are systems that convert energy from one form to mechanical energy, such as heat, electricity, or light. The most traditional actuator systems are internal combustion engines, steam engines, and now electric motors. In the human body, the conversion of chemical energy to mechanical energy under isothermal conditions is the basis of the body's ability to move, such as the reversible relaxation and contraction of muscles under the energy provided by ATP hydrolysis. All of these biological systems have extremely high energy conversion efficiencies, and animal muscles can convert more than 50% of food energy into useful work. The high efficiency of biological systems is largely due to the direct conversion of chemical energy, avoiding unnecessary intermediate processes that generate heat. Inspired by the physical adaptability, flexibility, reconfigurability, and versatility of mollusks and human muscles, actuators have been developed for a variety of applications, including artificial muscles, wearable devices, tactile devices, and medical devices.

[0003] Converting chemical energy into mechanical energy can use the chemical energy generated by proton transfer, charge transfer, redox, photoisomerization, phase transition, etc. to trigger conformational changes in polymer chains and achieve macroscopic driving of materials. At present, the driving systems using proton transfer are mainly concentrated in polycarboxylic acid systems. Carboxyl groups are deprotonated and negatively charged in alkaline solutions, so polycarboxylic acid molecular chains repel each other, which is manifested as material elongation in the macroscopic sense. In acidic solutions, carboxyl groups are protonated and uncharged, and polycarboxylic acids produce hydrogen bonds between molecular chains, which is manifested as material contraction in the macroscopic sense. The pH-driven systems that shrink in acid and elongate in alkali that are currently studied more are polyacrylic acid and polymethacrylic acid molecules. However, the construction of pH-driven systems that shrink in alkali and elongate in acid is still in a research gap. Unidirectional stimulus driving will lead to non-targeted movement during driving, and it is difficult to accurately control local and global movements. Therefore, it is necessary to design a pH driver with opposite stimulus behavior. The global movement can be programmed and combined with two pH-responsive drivers through gating, expanding the diversity and selectivity of the driving mechanism, making the driving effect more controlled, and better meeting the application scenarios in the fields of soft robots and artificial muscles.

[0004] At present, a variety of materials have been prepared as actuators, such as polymers, carbon nanotubes, graphene, organic-inorganic hybrid materials, etc. Therefore, actuators have also been made into various forms, such as three-dimensional blocks, two-dimensional films, one-dimensional fibers, etc. Among them, fiber actuators are a particularly attractive strategy because fibers have flexibility and highly anisotropic properties. In addition, animal movement is achieved through the contraction and extension of muscles, and muscles have a fiber structure. Muscle actuation is generated by the step-like movement of myosin motor proteins on actin filaments. When the movement of these very simple nanoscale motor proteins is converted into simple contraction / extension of muscles, a variety of different movements can be generated. Inspired by natural cases, we clearly realize that even simple changes in fiber length can cause very complex movements, which makes fiber actuators very valuable for research.

[0005] Therefore, it is of great significance to study a driving fiber that is pH-responsive and can achieve reversible and stable elongation and contraction and a preparation method thereof in order to solve the problems existing in the prior art. Summary of the invention

[0006] The purpose of the present invention is to solve the problems existing in the prior art and to provide a driving fiber with pH response and a preparation method thereof.

[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] A pH-responsive driving fiber has the property of contracting in an alkaline solution with a pH value of ≤11 and extending in an acidic solution with a pH value of ≥1 (when the pH is greater than 11, the fiber does not contract but extends; when the pH is less than 1, the fiber does not extend but contracts), and can continuously perform work by changing the pH value of the solution;

[0009] The pH-responsive driving fiber is a tannic acid-modified composite fiber, and the composite fiber is a polymer A / polyvinyl alcohol composite fiber;

[0010] Polymer A is a polymer having an amine group on the side chain;

[0011] In the polymer A / polyvinyl alcohol composite fiber, there is hydrogen bonding interaction between polyvinyl alcohol and polymer A to enhance the mechanical properties of the fiber;

[0012] Tannic acid and polymer A have covalent cross-linking effects to stabilize the shape and size of the fibers.

[0013] In alkaline solution, the side chain amine groups of polymer A are deprotonated, the hydrogen bonds between the molecular chains are restored, the molecular chains collapse, and the fibers shrink; in acidic solution, the side chain amine groups of polymer A are protonated, the molecular chains are electrostatically repelled, the molecular chains stretch, and the fibers elongate.

[0014] As the preferred technical solution:

[0015] In the pH-responsive driving fiber as described above, polymer A is chitosan, polyacrylamine or branched polyethyleneimine.

[0016] As described above, a pH-responsive driving fiber has a tensile strength of 1 to 5 MPa and an elongation at break of 80 to 120% in an acidic solution of pH = 1, and a tensile strength of 30 to 40 MPa in an alkaline solution of pH = 11 (the tensile strength test is carried out after the fiber is placed in an acidic / alkaline solution for equilibrium), and an elongation at break of 40 to 70%.

[0017] The pH-responsive actuating fiber as described above has a tensile strength varying between 1-5 MPa and 30-40 MPa, an elongation at break varying between 80-120% and 40-70%, and a work density stable at 5-20 kJ / m during 10 acid-base cycles (each acid-base cycle means being placed in an acidic solution first and then in an alkaline solution). 3 scope.

[0018] Its elongation and contraction behavior can be controlled by controlling the pH value in the environmental solution, and a variety of movements can be imitated, such as the driver actively lifting heavy objects, the relaxation-contraction movement of muscles, and the claw-shaped grasper.

[0019] The present invention also provides a method for preparing a driving fiber with pH response as described in any of the above items, wherein the polymer A / polyvinyl alcohol composite fiber is immersed in a tannic acid solution to swell, the pH value of the solution is adjusted to 8-9, and the solution is heated to 50-60°C, and oxygen is introduced. In the oxygen atmosphere, a covalent cross-linking reaction occurs between the tannic acid and the polymer A, and the product after the reaction is washed with deionized water and dried at room temperature to obtain a driving fiber with pH response.

[0020] As the preferred technical solution:

[0021] In the method for driving fibers with pH response as described above, the polymer A / polyvinyl alcohol composite fiber is obtained by squeezing a mixed solution of polymer A and polyvinyl alcohol as a spinning solution into an alkaline coagulation bath and then wet spinning.

[0022] A method for driving a fiber with pH response as described above, wherein the spinning solution is a uniform transparent solution obtained by mixing a polymer A solution with a polyvinyl alcohol solution for 10 to 12 hours, the concentration of the polymer A solution is 20 to 40 mg / mL, and the concentration of the polyvinyl alcohol solution is 100 to 200 mg / mL;

[0023] The alkaline coagulation bath refers to a NaOH solution with a concentration of 1 mol / L.

[0024] In the method for driving fibers with pH response as described above, the mass ratio of polymer A to polyvinyl alcohol is 2-4:1-2.

[0025] In the method for driving a fiber with pH response as described above, the concentration of the tannic acid solution is 20-40 mg / mL; the mass ratio of tannic acid to polymer A is 1-2:1-2.

[0026] In the method for driving a pH-responsive fiber as described above, the polymer A / polyvinyl alcohol composite fiber is immersed in a tannic acid solution for 30 minutes, oxygen is introduced into the tannic acid solution, and the immersion is continued for 1 to 6 hours.

[0027] The principle of the present invention is:

[0028] The polymer A of the present invention refers to a type of polymer with an amine group on the side chain, which can be deprotonated in an alkaline solution, the molecular chain collapses, and protonated in an acidic solution, the molecular chain stretches, and has pH responsiveness. The polymer A and polyvinyl alcohol are processed into fibers using a wet spinning method. Polyvinyl alcohol and polymer A form hydrogen bond interactions, which can enhance the mechanical properties of the fiber. Finally, a tannic acid cross-linking network is introduced into the fiber, so that the fiber can always maintain dimensional stability in strong acids and alkalis.

[0029] In the driving fiber of the present invention, when the fiber is immersed in an acidic solution, the amine groups in the side chains of polymer A are protonated and positively charged. Due to the electrostatic repulsion, the molecular chain stretches, the tensile strength of the fiber decreases, and the fiber macroscopically manifests as elongation. When immersed in an alkaline solution, the amine groups in the side chains of polymer A are deprotonated, the molecular chain is uncharged, hydrogen bonds interact between molecules, the molecular chain collapses, the tensile strength of the fiber increases, and the fiber macroscopically manifests as contraction. If the fiber is not cross-linked with tannic acid, it will completely dissolve in the water environment after entering the acidic solution, and the driving stability cannot be maintained. And a large number of experiments have shown that only fibers formed by the composite of polymer A, polyvinyl alcohol and tannic acid can achieve the above-mentioned effect, and if polyvinyl alcohol or tannic acid is replaced with other substances, the ideal effect cannot be achieved.

[0030] Beneficial effects:

[0031] (1) The pH-responsive driving fiber of the present invention can effectively control the elongation and contraction behavior of the device by controlling the pH value of the solution. The maximum pH driving range is pH 1 to 11, and it has a faster driving rate in strong acids and bases.

[0032] (2) A pH-responsive driving fiber of the present invention has a tensile strength between 1 and 5 MPa and 30 and 40 MPa after 10 acid-base cycles, and a work density of 5 to 20 kJ / m 3 .

[0033] (3) The present invention provides a method for preparing a pH-responsive actuating fiber, which constructs an actuating fiber with excellent performance in a simple and green way, and its maximum work density is 20 kJ / m 3 . BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of pH-responsive actuating fibers actively lifting heavy objects;

[0035] Figure 2 Schematic diagram of the relaxation-contraction motion of a pH-responsive actuating fiber simulating muscle;

[0036] Figure 3 Schematic diagram of a pH-responsive actuating fiber used as a claw-shaped gripper. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0038] The performance index testing / calculation method involved in the present invention is as follows:

[0039] The tensile strength was tested using a universal testing machine (model: UTM2502, Suns), and the test standard was based on GB / T1040.3-2006.

[0040] Work density: Calculate using the following formula W = (L d -L c )(m c -ρ s V c )g / V f , where L d is the length of the fiber extended in alkaline solution, L c is the length of the fiber contracted in the acid solution, m c is the mass of the load, ρ s is the density of the aqueous solution, ρ s =1.0g / cm 3 , V cis the volume of the load, g is the acceleration due to gravity, g = 9.8 N / kg, V f is the fiber volume.

[0041] Example 1

[0042] A method for preparing a pH-responsive actuating fiber, comprising the following steps:

[0043] (1) Preparation of raw materials:

[0044] Polymer A: chitosan (manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., brand: C105799);

[0045] Polyvinyl alcohol: Manufacturer: Thermo Fisher Scientific, brand number: 041242.22;

[0046] Tannic acid;

[0047] NaOH solution;

[0048] (2) mixing the polymer A aqueous solution with the polyvinyl alcohol aqueous solution for 10 hours to obtain a uniform transparent solution, which is the spinning solution;

[0049] The mass ratio of polymer A to polyvinyl alcohol is 2:1; the concentration of the polymer A aqueous solution is 20 mg / mL, and the concentration of the polyvinyl alcohol aqueous solution is 100 mg / mL;

[0050] (3) extruding the spinning solution of step (2) into a 1 mol / L NaOH solution, and obtaining polymer A / polyvinyl alcohol composite fibers by wet spinning; in the polymer A / polyvinyl alcohol composite fibers, there is hydrogen bonding interaction between polyvinyl alcohol and polymer A;

[0051] The wet spinning process parameters were as follows: extrusion speed 0.8 mL / min, needle specifications: inner diameter 0.34 mm, outer diameter 0.64 mm, total needle length 30 mm;

[0052] (4) The polymer A / polyvinyl alcohol composite fiber was immersed in a 30 mg / mL tannic acid aqueous solution for 30 min to swell, and then the pH value of the solution was adjusted to 8, and the solution was heated to 50°C, oxygen was introduced, and the immersion was continued for 6 h. In the oxygen atmosphere, a covalent cross-linking reaction occurred between the tannic acid and the polymer A. The reaction product was washed with deionized water and dried at room temperature to obtain a pH-responsive actuating fiber.

[0053] Wherein, the mass ratio of tannic acid to polymer A is 1:1.

[0054] The pH-responsive actuating fiber finally obtained has the property of shrinking in alkaline solution with pH value ≤ 11 and stretching in acidic solution with pH value ≥ 1; the pH-responsive actuating fiber has a tensile strength of 2MPa and an elongation at break of 80% in hydrochloric acid solution with pH = 1, and a tensile strength of 40MPa and an elongation at break of 40% in sodium hydroxide solution with pH = 11; during 10 acid-base cycles, the tensile strength of the pH-responsive actuating fiber varies between 2MPa and 40MPa, and the work density is stabilized at 12kJ / m 3 .

[0055] like Figure 1 As shown, the driving fiber prepared above can be used as a soft robot to actively lift and carry heavy objects in alkaline solutions, and to directionally transport heavy objects in acidic solutions.

[0056] like Figure 2 As shown, the driving fibers prepared above can be used as artificial antagonist muscles and agonist muscles in the field of soft robotics.

[0057] like Figure 3 As shown, the driving fiber prepared above is used as a claw-shaped extractor to actively grab objects in an alkaline solution.

[0058] Comparative Example 1

[0059] A driving fiber is basically the same as Example 1, except that the operation of step (2) is omitted and the aqueous solution of polymer A is directly used as the spinning solution in step (3).

[0060] The final fiber breaking elongation is 5%, and the fiber is too brittle and easy to break, and cannot be used in practice.

[0061] By comparing Comparative Example 1 with Example 1, it can be found that the fiber cannot resist bending and twisting in actual operation, and the fiber is too brittle and easily broken. This is because the chitosan molecule is a rigid structure, and the fiber becomes more brittle after being directly cross-linked with tannic acid.

[0062] Comparative Example 2

[0063] A driving fiber is basically the same as Example 1, except that the tannic acid solution in step (4) is replaced by a boric acid solution.

[0064] The final actuating fiber is dissolved in a hydrochloric acid solution with a pH of 1, and has a tensile strength of 15 MPa in a sodium hydroxide solution with a pH of 11.

[0065] By comparing Comparative Example 2 with Example 1, it can be found that Comparative Example 2 dissolves in a solution with a pH lower than 2. This is because boric acid is mainly cross-linked on two adjacent hydroxyl groups of polyvinyl alcohol and cannot cross-link the polymer A network. Therefore, polymer A will dissolve in an acidic solution.

[0066] Comparative Example 3

[0067] A driving fiber is basically the same as Example 1, except that the tannic acid solution in step (4) is replaced by glutaraldehyde solution.

[0068] The final driving fiber has an elongation at break of 3%. The fiber is too brittle and easy to break, and cannot be used in practice.

[0069] By comparing Comparative Example 3 with Example 1, it can be found that the fiber is too brittle and cannot be driven. This is because the degree of cross-linking between glutaraldehyde and chitosan is large, which restricts the movement of the molecular chain and limits the extension of the molecular chain.

[0070] Comparative Example 4

[0071] A pH-responsive driving fiber is basically the same as Example 1, except that the polyvinyl alcohol solution in step (2) is replaced by a gelatin solution (manufacturer: Sinopharm Chemical Reagent Co., Ltd., brand number: 10010326), and the tannic acid solution in step (4) is replaced by a genipin solution.

[0072] The final pH-responsive driving fiber has a tensile strength of 1 MPa in a hydrochloric acid solution with a pH of 1 and a tensile strength of 8 MPa in a sodium hydroxide solution with a pH of 11; during ten acid-base cycles, the fiber tensile strength gradually decreases, and the final tensile strength will be 10 kPa, making it unable to perform work stably.

[0073] By comparing Comparative Example 4 with Example 1, it can be found that the driving fiber cannot stably perform work in multiple cycles of driving. This is because the cross-linking of genipin depends on the pH value of the solution, and genipin is a degradable biomolecule, so its cross-linking effect has poor stability.

[0074] Example 2

[0075] A method for preparing a pH-responsive actuating fiber, the specific steps are as follows:

[0076] (1) Preparation of raw materials:

[0077] Polymer A: polyacrylamine (manufacturer: Sigma-Aldrich, brand: S#479136);

[0078] Polyvinyl alcohol: Manufacturer: Thermo Fisher Scientific, Brand: 041242.22;

[0079] Tannic acid;

[0080] NaOH solution;

[0081] (2) mixing the polymer A aqueous solution with the polyvinyl alcohol aqueous solution for 11 hours to obtain a uniform transparent solution, which is the spinning solution;

[0082] The mass ratio of polymer A to polyvinyl alcohol is 3:1; the concentration of the polymer A aqueous solution is 20 mg / mL, and the concentration of the polyvinyl alcohol aqueous solution is 150 mg / mL;

[0083] (3) extruding the spinning solution of step (2) into a 1 mol / L NaOH solution, and obtaining polymer A / polyvinyl alcohol composite fibers by wet spinning; in the polymer A / polyvinyl alcohol composite fibers, there is hydrogen bonding interaction between polyvinyl alcohol and polymer A;

[0084] The wet spinning process parameters are as follows: extrusion speed 0.8 mL / min, needle specifications: inner diameter 0.34 mm, outer diameter 0.64 mm, total needle length 30 mm.

[0085] (4) The polymer A / polyvinyl alcohol composite fiber was immersed in a 20 mg / mL tannic acid aqueous solution for 30 min to swell, and then the pH value of the solution was adjusted to 8.2, and the solution was heated to 52°C, oxygen was introduced, and the immersion was continued for 5 h. In the oxygen atmosphere, a covalent cross-linking reaction occurred between the tannic acid and the polymer A. The reaction product was washed with deionized water and dried at room temperature to obtain a pH-responsive actuating fiber.

[0086] Wherein, the mass ratio of tannic acid to polymer A is 1:2.

[0087] The pH-responsive actuating fiber finally obtained has the property of shrinking in alkaline solution with pH value ≤ 11 and stretching in acidic solution with pH value ≥ 1; the pH-responsive actuating fiber has a tensile strength of 1MPa and a breaking elongation of 120% in hydrochloric acid solution with pH = 1, and a tensile strength of 30MPa and a breaking elongation of 50% in sodium hydroxide solution with pH = 11; during 10 acid-base cycles, the tensile strength of the pH-responsive actuating fiber varies between 1MPa and 30MPa, and the work density is stable at 5kJ / m 3 .

[0088] Example 3

[0089] A method for preparing a pH-responsive actuating fiber, the specific steps are as follows:

[0090] (1) Preparation of raw materials:

[0091] Polymer A: branched polyethyleneimine (manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., brand: P434400);

[0092] Polyvinyl alcohol: Manufacturer: Thermo Fisher Scientific, Brand: 041242.22;

[0093] Tannic acid;

[0094] NaOH solution;

[0095] (2) mixing the polymer A aqueous solution with the polyvinyl alcohol aqueous solution for 12 hours to obtain a uniform transparent solution, which is the spinning solution;

[0096] The mass ratio of polymer A to polyvinyl alcohol is 1:1; the concentration of the polymer A aqueous solution is 40 mg / mL, and the concentration of the polyvinyl alcohol aqueous solution is 200 mg / mL;

[0097] (3) extruding the spinning solution of step (2) into a 1 mol / L NaOH solution, and obtaining polymer A / polyvinyl alcohol composite fibers by wet spinning; in the polymer A / polyvinyl alcohol composite fibers, there is hydrogen bonding interaction between polyvinyl alcohol and polymer A;

[0098] The wet spinning process parameters are as follows: extrusion speed 0.8 mL / min, needle specifications: inner diameter 0.34 mm, outer diameter 0.64 mm, total needle length 30 mm.

[0099] (4) The polymer A / polyvinyl alcohol composite fiber was immersed in a 40 mg / mL tannic acid aqueous solution for 30 min to swell, and then the pH value of the solution was adjusted to 8.5, and the solution was heated to 54°C, oxygen was introduced, and the immersion was continued for 4 h. In the oxygen atmosphere, a covalent cross-linking reaction occurred between the tannic acid and the polymer A. The reaction product was washed with deionized water and dried at room temperature to obtain a pH-responsive actuating fiber.

[0100] Wherein, the mass ratio of tannic acid to polymer A is 1:1.

[0101] The pH-responsive actuating fiber finally obtained has the property of shrinking in alkaline solution with pH value ≤ 11 and stretching in acidic solution with pH value ≥ 1; the pH-responsive actuating fiber has a tensile strength of 5MPa and an elongation at break of 120% in hydrochloric acid solution with pH = 1, and a tensile strength of 40MPa and an elongation at break of 40% in sodium hydroxide solution with pH = 11; during 10 acid-base cycles, the tensile strength of the pH-responsive actuating fiber varies between 5MPa and 40MPa, and the work density is stabilized at 20kJ / m 3 .

[0102] Example 4

[0103] A method for preparing a pH-responsive actuating fiber, comprising the following steps:

[0104] (2) Preparation of raw materials:

[0105] Polymer A: chitosan (manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., brand: C105799);

[0106] Polyvinyl alcohol: Manufacturer: Thermo Fisher Scientific, brand number: 041242.22;

[0107] Tannic acid;

[0108] NaOH solution;

[0109] (2) mixing the polymer A aqueous solution with the polyvinyl alcohol aqueous solution for 10.5 hours to obtain a uniform transparent solution, which is the spinning solution;

[0110] The mass ratio of polymer A to polyvinyl alcohol is 3:2; the concentration of the polymer A aqueous solution is 30 mg / mL, and the concentration of the polyvinyl alcohol aqueous solution is 100 mg / mL;

[0111] (3) extruding the spinning solution of step (2) into a 1 mol / L NaOH solution, and obtaining polymer A / polyvinyl alcohol composite fibers by wet spinning; in the polymer A / polyvinyl alcohol composite fibers, there is hydrogen bonding interaction between polyvinyl alcohol and polymer A;

[0112] The wet spinning process parameters are as follows: extrusion speed 0.8 mL / min, needle specifications: inner diameter 0.34 mm, outer diameter 0.64 mm, total needle length 30 mm.

[0113] (4) The polymer A / polyvinyl alcohol composite fiber was immersed in a tannic acid solution with a concentration of 20 mg / mL for 30 minutes to swell, and then the pH value of the solution was adjusted to 8.7, and the solution was heated to 56°C, oxygen was introduced, and the immersion was continued for 3 hours. In the oxygen atmosphere, a covalent cross-linking reaction occurred between the tannic acid and the polymer A. The reaction product was washed with deionized water and dried at room temperature to obtain a pH-responsive actuating fiber.

[0114] Wherein, the mass ratio of tannic acid to polymer A is 1:2.

[0115] The pH-responsive actuating fiber finally obtained has the property of shrinking in alkaline solution with pH value ≤ 11 and stretching in acidic solution with pH value ≥ 1; the pH-responsive actuating fiber has a tensile strength of 5MPa and an elongation at break of 90% in hydrochloric acid solution with pH = 1, and a tensile strength of 35MPa and an elongation at break of 60% in sodium hydroxide solution with pH = 11; during 10 acid-base cycles, the tensile strength of the pH-responsive actuating fiber varies between 5MPa and 35MPa, and the work density is stabilized at 15kJ / m 3 .

[0116] Example 5

[0117] A method for preparing a pH-responsive actuating fiber, the specific steps are as follows:

[0118] (3) Preparation of raw materials:

[0119] Polymer A: polyacrylamine (manufacturer: Sigma-Aldrich, brand: S#479136);

[0120] Polyvinyl alcohol: Manufacturer: Thermo Fisher Scientific, Brand: 041242.22;

[0121] Tannic acid;

[0122] NaOH solution;

[0123] (2) mixing the polymer A aqueous solution with the polyvinyl alcohol aqueous solution for 11 hours to obtain a uniform transparent solution, which is the spinning solution;

[0124] The mass ratio of polymer A to polyvinyl alcohol is 4:1; the concentration of the polymer A aqueous solution is 30 mg / mL, and the concentration of the polyvinyl alcohol aqueous solution is 150 mg / mL;

[0125] (3) extruding the spinning solution of step (2) into a 1 mol / L NaOH solution, and obtaining polymer A / polyvinyl alcohol composite fibers by wet spinning; in the polymer A / polyvinyl alcohol composite fibers, there is hydrogen bonding interaction between polyvinyl alcohol and polymer A;

[0126] The wet spinning process parameters are as follows: extrusion speed 0.8 mL / min, needle specifications: inner diameter 0.34 mm, outer diameter 0.64 mm, total needle length 30 mm.

[0127] (4) The polymer A / polyvinyl alcohol composite fiber was immersed in a 30 mg / mL tannic acid aqueous solution for 30 min to swell, and then the pH value of the solution was adjusted to 8.9, and the solution was heated to 58°C, oxygen was introduced, and the immersion was continued for 2 h. In the oxygen atmosphere, a covalent cross-linking reaction occurred between the tannic acid and the polymer A. The reaction product was washed with deionized water and dried at room temperature to obtain a pH-responsive actuating fiber.

[0128] Wherein, the mass ratio of tannic acid to polymer A is 1:1.

[0129] The pH-responsive actuating fiber finally obtained has the property of shrinking in alkaline solution with pH value ≤ 11 and stretching in acidic solution with pH value ≥ 1; the pH-responsive actuating fiber has a tensile strength of 1MPa and a breaking elongation of 120% in hydrochloric acid solution with pH = 1, and a tensile strength of 30MPa and a breaking elongation of 70% in sodium hydroxide solution with pH = 11; during 10 acid-base cycles, the tensile strength of the pH-responsive actuating fiber varies between 1MPa and 30MPa, and the work density is stable at 10kJ / m 3 .

[0130] Example 6

[0131] A method for preparing a pH-responsive actuating fiber, comprising the following steps:

[0132] (4) Preparation of raw materials:

[0133] Polymer A: branched polyethyleneimine (manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., brand: P434400);

[0134] Polyvinyl alcohol: Manufacturer: Thermo Fisher Scientific, brand number: 041242.22;

[0135] Tannic acid;

[0136] NaOH solution;

[0137] (2) mixing the polymer A aqueous solution with the polyvinyl alcohol aqueous solution for 11.5 hours to obtain a uniform transparent solution, which is the spinning solution;

[0138] The mass ratio of polymer A to polyvinyl alcohol is 2:1; the concentration of the polymer A aqueous solution is 40 mg / mL, and the concentration of the polyvinyl alcohol aqueous solution is 200 mg / mL;

[0139] (3) extruding the spinning solution of step (2) into a 1 mol / L NaOH solution, and obtaining polymer A / polyvinyl alcohol composite fibers by wet spinning; in the polymer A / polyvinyl alcohol composite fibers, there is hydrogen bonding interaction between polyvinyl alcohol and polymer A;

[0140] The wet spinning process parameters are as follows: extrusion speed 0.8 mL / min, needle specifications: inner diameter 0.34 mm, outer diameter 0.64 mm, total needle length 30 mm.

[0141] (4) The polymer A / polyvinyl alcohol composite fiber was immersed in a 40 mg / mL tannic acid aqueous solution for 30 min to swell, and then the pH value of the solution was adjusted to 9, and the solution was heated to 60°C, oxygen was introduced, and the immersion was continued for 1 h. In the oxygen atmosphere, a covalent cross-linking reaction occurred between the tannic acid and the polymer A. The reaction product was washed with deionized water and dried at room temperature to obtain a pH-responsive actuating fiber.

[0142] Wherein, the mass ratio of tannic acid to polymer A is 1:2.

[0143] The pH-responsive actuating fiber finally obtained has the property of shrinking in alkaline solution with pH value ≤ 11 and stretching in acidic solution with pH value ≥ 1; the pH-responsive actuating fiber has a tensile strength of 3MPa and an elongation at break of 120% in hydrochloric acid solution with pH = 1, and a tensile strength of 35MPa and an elongation at break of 65% in sodium hydroxide solution with pH = 11; during 10 acid-base cycles, the tensile strength of the pH-responsive actuating fiber varies between 3MPa and 35MPa, and the work density is stabilized at 18kJ / m 3 .

Claims

1. A pH-responsive actuating fiber, characterized in that: It has the property of shrinking in alkaline solution with pH value ≤ 11 and stretching in acidic solution with pH value ≥ 1; The pH-responsive driving fiber is a tannic acid-modified composite fiber, and the composite fiber is a polymer A / polyvinyl alcohol composite fiber; Polymer A is a polymer having an amine group on the side chain; In the polymer A / polyvinyl alcohol composite fiber, there is a hydrogen bonding interaction between polyvinyl alcohol and polymer A; There is a covalent cross-linking effect between tannic acid and polymer A.

2. A pH-responsive actuating fiber according to claim 1, characterized in that: The polymer A is chitosan, polyacrylamine or branched polyethyleneimine.

3. The pH-responsive actuating fiber according to claim 1, characterized in that: The pH-responsive actuating fiber has a tensile strength of 1 to 5 MPa and an elongation at break of 80 to 120% in an acidic solution of pH=1, and a tensile strength of 30 to 40 MPa and an elongation at break of 40 to 70% in an alkaline solution of pH=11.

4. A pH-responsive actuating fiber according to claim 3, characterized in that: During 10 acid-base cycles, the tensile strength of the pH-responsive actuating fibers varied between 1-5 MPa and 30-40 MPa, the elongation at break varied between 80-120% and 40-70%, and the work density was stable at 5-20 kJ / m 3 scope.

5. A method for preparing a pH-responsive actuating fiber as claimed in any one of claims 1 to 4, characterized in that: After the polymer A / polyvinyl alcohol composite fiber is immersed in a tannic acid solution to swell, the pH value of the solution is adjusted to 8-9 and heated to 50-60°C. Oxygen is introduced. In the oxygen atmosphere, a covalent cross-linking reaction occurs between tannic acid and polymer A. The reaction product is washed with deionized water and dried to obtain a pH-responsive driving fiber.

6. A method for driving a pH-responsive fiber according to claim 5, characterized in that: The polymer A / polyvinyl alcohol composite fiber is obtained by squeezing a mixed solution of polymer A and polyvinyl alcohol as a spinning solution into an alkaline coagulation bath and performing wet spinning.

7. A method for driving a pH-responsive fiber according to claim 6, characterized in that: The spinning solution is a uniform transparent solution obtained by mixing a polymer A solution and a polyvinyl alcohol solution for 10 to 12 hours, wherein the concentration of the polymer A solution is 20 to 40 mg / mL, and the concentration of the polyvinyl alcohol solution is 100 to 200 mg / mL; The alkaline coagulation bath refers to a NaOH solution with a concentration of 1 mol / L.

8. The method for driving a pH-responsive fiber according to claim 7, characterized in that: The mass ratio of polymer A to polyvinyl alcohol is 2-4:1-2.

9. The method for driving a pH-responsive fiber according to claim 5, characterized in that: The concentration of the tannic acid solution is 20-40 mg / mL; the mass ratio of tannic acid to polymer A is 1-2:1-2.

10. The method for driving a pH-responsive fiber according to claim 5, characterized in that: After the polymer A / polyvinyl alcohol composite fiber is immersed in the tannic acid solution for 30 minutes, oxygen is introduced into the tannic acid solution and the fiber is immersed for another 1 to 6 hours.

Citation Information

Patent Citations

  • Method for preparing high-strength chitosan fiber

    CN103993380A

  • Preparation method of cross-linked macromolecule hydrogen bond composite fiber

    CN111058103A

  • Polyelectrolyte compound hydrogel fiber and preparation method thereof

    CN113638078A

  • Preparation method of high-strength self-healing antibacterial hydrogel loaded with tannic acid

    CN116407674A

Cited By

  • PVA fiber reinforced geopolymer material and preparation method thereof

    CN121085581A